2020
DOI: 10.1093/mnras/staa1032
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength cross-correlation analysis of the simulated cosmic web

Abstract: We used magnetohydrodynamical cosmological simulations to investigate the cross-correlation between different observables (i.e. X-ray emission, Sunyaev–Zeldovich (SZ) signal at 21 cm, H i temperature decrement, diffuse synchrotron emission, and Faraday Rotation) as a probe of the diffuse matter distribution in the cosmic web. We adopt a uniform and simplistic approach to produce synthetic observations at various wavelengths, and we compare the detection chances of different combinations of observables correlat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…We also repeated the above procedure for a different set of simulations, described in Gheller & Vazza (2020). These simulations are lower resolution (83 kpc pixel size, 85 3 Mpc 3 total volume) but include different physical scenarios such as : an astrophysical scenario with B injected by AGNs and star-forming regions, following the cosmic star formation history; a primordial model with a stronger primordial magnetic field of 1 nG; and a dynamo model in which at run-time intracluster medium-like amplification of magnetic fields is assumed, included within filaments.…”
Section: Cosmological Simulationsmentioning
confidence: 99%
“…We also repeated the above procedure for a different set of simulations, described in Gheller & Vazza (2020). These simulations are lower resolution (83 kpc pixel size, 85 3 Mpc 3 total volume) but include different physical scenarios such as : an astrophysical scenario with B injected by AGNs and star-forming regions, following the cosmic star formation history; a primordial model with a stronger primordial magnetic field of 1 nG; and a dynamo model in which at run-time intracluster medium-like amplification of magnetic fields is assumed, included within filaments.…”
Section: Cosmological Simulationsmentioning
confidence: 99%
“…Vernstrom et al (2017) reported no significant detection of cross-correlation between galaxies and radio emission on ≥20 arcmin scales, and used this information to derive upper limits on the typical magnetization of filaments of the cosmic web. In Gheller & Vazza (2020), we introduced a procedure to simulate the crosscorrelation between the diffuse radio emission at 180 MHz and the projected galaxy distribution in the simulation. In particular, we set the threshold of projected DM density to ρ th = 6 × 10 −29 g cm −3 in order to produce a number of galaxies (i.e.…”
Section: Comparison To Available Radio Observablesmentioning
confidence: 99%
“…Following Gheller & Vazza (2020), the normalized correlation matrix C between 2D N × M pixels images A and B is evaluated through…”
Section: Comparison To Available Radio Observablesmentioning
confidence: 99%
“…Martizzi et al (2019) analyse the gas content and separated gas into different phases of the various structures of the cosmic web at different redshifts of the IllustrisTNG simulation (Nelson et al 2019). More recently, Gheller & Vazza (2020) show that one of the most promising tracers of gas in the diffuse warm-hot intergalactic medium (WHIM) around filaments is the Sunyaev-Zel'dovich (SZ) effect, thanks to its linear dependence on gas pressure.…”
Section: Introductionmentioning
confidence: 99%